2023
DOI: 10.1055/s-0043-1768598
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Normal Saline versus PlasmaLyte on Coagulation and Metabolic Status in Patients Undergoing Neurosurgical Procedures

Abstract: Background The choice of intraoperative fluid in neurosurgical patients is important as we need to maintain adequate cerebral perfusion and oxygenation and also avoid cerebral edema. Normal saline (NS) is commonly used in neurosurgeries, but it leads to hyperchloremic metabolic acidosis, which may result in coagulopathy. Balanced crystalloid with physiochemical composition akin to that of plasma has favorable effects on metabolic profile and may avoid the problems associated with NS. Against this background, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…In two recent RCTs comparing Plasmalyte and NS in neurosurgical patients, including only TBI patients, the authors found that Plasmalyte maintained the metabolic profile better than 0.9% saline. [ 2 16 ] Our results were in agreement with these two studies. In a subgroup analysis of the BaSICS RCT conducted on TBI patients, the authors found that using BCs was associated with a higher 90-day mortality.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In two recent RCTs comparing Plasmalyte and NS in neurosurgical patients, including only TBI patients, the authors found that Plasmalyte maintained the metabolic profile better than 0.9% saline. [ 2 16 ] Our results were in agreement with these two studies. In a subgroup analysis of the BaSICS RCT conducted on TBI patients, the authors found that using BCs was associated with a higher 90-day mortality.…”
Section: Discussionsupporting
confidence: 93%
“…[ 1 ] Although 0.9% normal saline (NS) has been traditionally favoured in neurosurgical patients, its supraphysiological chloride content can lead to hyperchloremic metabolic acidosis and acute kidney injury (AKI) when infused in larger volumes (>2 l). [ 2 3 ] This, coupled with renal ischaemia and reduced glomerular filtration rate (GFR), heightens the risk of AKI. In addition, physiological derangements produced by overzealous IV fluid administration may necessitate further crystalloid and blood product infusions, establishing a vicious cycle.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, authors observed that chloride levels in the 0.9 % saline group were persistently higher than the Plasmalyte A group throughout the study period. 9,12 Similarly, rise in chloride levels (up to 115 mEq/L) was noted in patients undergoing surgery for supratentorial tumors when NS was used. 7 In literature, 0.9 % saline is known to cause hyperchloremic metabolic acidosis.…”
Section: Discussionmentioning
confidence: 96%
“…In a similar study in neurosurgical population, creatinine was significantly elevated in NS group at 4 hours after surgery. 9 The urine NGAL and serum cystatin C emerged as biomarkers of AKI in medical literature. 10,11 Urine NGAL is an early biomarker of AKI seen to rise as early as 6 hours after insult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation